Downscaling land‐use data to provide global 30″ estimates of five land‐use classes. Issue 9 (30th March 2016) - Hoskins, Andrew J.; Bush, Alex; Gilmore, James; Harwood, Tom; Hudson, Lawrence N.; Ware, Chris; Williams, Kristen J.; Ferrier, Simon
Abstract: Land‐use change is one of the biggest threats to biodiversity globally. The effects of land use on biodiversity manifest primarily at local scales which are not captured by the coarse spatial grain of current global land‐use mapping. Assessments of land‐use impacts on biodiversity across large spatial extents require data at a similar spatial grain to the ecological processes they are assessing. Here, we develop a method for statistically downscaling mapped land‐use data that combines generalized additive modeling and constrained optimization. This method was applied to the 0.5° Land‐use Harmonization data for the year 2005 to produce global 30″ (approx. 1 km 2 ) estimates of five land‐use classes: primary habitat, secondary habitat, cropland, pasture, and urban. The original dataset was partitioned into 61 bio‐realms (unique combinations of biome and biogeographical realm) and downscaled using relationships with fine‐grained climate, land cover, landform, and anthropogenic influence layers. The downscaled land‐use data were validated using the PREDICTS database and the geoWiki global cropland dataset. Application of the new method to all 61 bio‐realms produced global fine‐grained layers from the 2005 time step of the Land‐use Harmonization dataset. Coarse‐scaled proportions of land use estimated from these data compared well with those estimated in the original datasets (mean R 2 : 0.68 ± 0.19). Validation with the PREDICTS database showed the new downscaled land‐use layers improved discrimination of all five classes at PREDICTS sites ( P < 0.0001 in all cases). Additional validation of the downscaled cropping layer with the geoWiki layer showed an R 2 improvement of 0.12 compared with the Land‐use Harmonization data. The downscaling method presented here produced the first global land‐use dataset at a spatial grain relevant to ecological processes that drive changes in biodiversity over space and time. Integrating these data with biodiversity measures will enable the reporting of land‐use impacts on biodiversity at a finer resolution than previously possible. Furthermore, the general method presented here could be useful to others wishing to downscale similarly constrained coarse‐resolution data for other environmental variables. Abstract : Current global land‐use data are at a coarse spatial grain which does not match the local ecological processes that they disrupt. Here, we present a new statistical downscaling method and apply this method to a global 0.5 degree land‐use dataset. Using our method, we produce a global fine‐grained land‐use dataset at a spatial resolution more relevant to the local ecological processes that land‐use practices disrupt.